Storage studies on preservation of banana and its production - Sindu Bhaskar (Department of Farm power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 2000)
The primary objective of this study was to conduct shelf lite studies like vacuum packing and nitrogen packing on storage of banana and its products and to suggest optimum storage conditions. The study mainly concentrated on development of equipments for optimising the processing and storage conditions. A constant temperature frying pan was developed for optimising the frying temperature, duration and type of oil. The capacity of the constant temperature frying pan is 100 kg of raw banana per day of 8 h. A low cost set up for nitrogen packing was also developed. Vacuum packing as well as nitrogen packing can be done satisfactorily. Raw banana stored under vacuum cum refrigerated packing showed maximum shelf life up to 20 days without any quality deterioration. The chips fried in coconut oil at a temperature 115 QC for a duration 15 min stored under nitrogen packing showed best results followed by chips fried in coconut oil at a temperature 105 QC for 20 min under . . nitrogen packing. These results were on the basis of organoleptic evaluation. Jaggery coated chips and banana powder stored under nitrogen packing was the best among four treatments after storage of two months. The economic analysis showed the cost of entire operation for the processing of chips was Rs.57.5 per kg of chips. /' The moisture content of 'taw banana have significant effect on cooking duration therefore the moisture content of banana slices prepared for chips making should be standardised. The peeling and slicing operations are done manually. The speed of the labourers have considerable effect on capacity of constant temperature frying pan.